Recyclable Palladium-Catalyzed Carbonylative Coupling of Aryl Halides and Organoaluminum Compounds with tert-Butyl Isocyanide as CO Equivalent Leading to 1,2-Diketones - Tu, Zhiyuan; Zhan, Jianan; You, Shengyong; Cai, Mingzhong (Synthesis, 2024)
An efficient heterogeneous palladium-catalyzed carbonylative coupling of aryl halides and organoaluminum compounds has been developed using tert-butyl isocyanide as CO equivalent. The carbonylation reaction proceeds smoothly in toluene with KOtBu as a base at 100 °C by using 10 mol% of an SBA-15-anchored bidentate phosphine palladium(0) complex [2P-SBA-15-Pd(0)] as the catalyst and provides a general and practical approach for the assembly of 1,2-diketones in good to excellent yields. This heterogenized palladium catalyst can be readily separated and recovered via a simple centrifugation process and reused for more than seven cycles with almost consistent catalytic efficiency.
Keywords: palladium; carbonylative coupling; organoaluminum reagents; 1,2-diketones; heterogeneous catalysis